Hydromechanical behaviour of a slope reinforced by grass roots under rainfall conditions - Prasetyaningtiyas, Gayuh Aji; Kamchoom, Viroon; Leung, Anthony Kwan; Likitlersuang, Suched (My University, 2024)
Soil bioengineering using vegetation has been considered an environmentally friendly solution to improve slope stability. Although several studies have demonstrated the contribution of vegetation to slope stability, a gap in understanding the mechanisms of grass root–soil interactions under rainfall conditions remains. This study investigates the effects of the roots of vetiver grass (Chrysopogon zizanioides) on the hydromechanical behaviour of an unsaturated soil slope using the centrifuge modelling technique. The changes in pore water pressure and slope deformation were monitored during the test. The monitored data were subsequently back-analysed and interpreted using seepage–stability analyses. In addition, this study focused on evaluating the effect of roots on slope stability, considering safety and pore water pressure during rainfall. Results revealed that the vetiver roots remarkably affected the initial suction of the slope by increasing the soil's air-entry value. The increased suction and the additional cohesion provided by the roots enhanced slope stability under rainfall conditions.
Keywords: Centrifuge modelling; Rainfall infiltration; Root reinforcement; Slope stability; Vegetation